A catalyst for removing trace oxygen from a hydrogen-rich olefin gas, a preparation method thereof, and a catalytic removal method

CN122999192APending Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510553288.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

其原因是:考虑到脱氧反应的反应热以及由此可能引发的氢气和烯烃的加成反应等副反应问题,导致过程的不可控以及对脱氧效果和脱氧剂的破坏

Benefits of technology

[0063]本发明提供的催化剂是整体式催化剂,有别于颗粒状或条状催化剂,本发明提供的整体式催化剂在使用时无需采用堆积反应方式,这有助于热量的散发及对副反应的抑制。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of gas purification, and more particularly to a catalyst for removing trace oxygen from hydrogen-rich olefin gas, a preparation method thereof and a catalytic removal method. The present application obtains a new catalyst by adopting the following technical means: using a monolithic carrier, coating an alumina coating on the surface of the carrier, and adjusting the content of main active components and active aids in the catalyst. Different from granular or strip-shaped catalysts, the catalyst provided by the present application does not need to adopt a stacking reaction mode when used, which is helpful for heat dissipation and inhibition of side reactions. When the catalyst of the present application is used to remove trace oxygen from hydrogen-rich olefin raw gas, the hydrogen-rich olefin raw gas can be directly contacted with the catalyst of the present application, the process is simple, the required reaction temperature is low, the olefin retention rate is high, and the deoxygenation effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gas purification technology, and more specifically, to a catalyst for removing trace amounts of oxygen from hydrogen-rich olefin gases, its preparation method, and its catalytic removal method. Background Technology

[0002] In the industrial production of polyolefins, the presence of trace amounts of oxygen in olefin gases can destroy the active sites of catalysts, or allow oxygen to participate in the polymerization reaction, reducing the directional conversion capacity of the polymerization catalyst or generating oxygen-containing random active chains. This not only reduces the selectivity, activity, and conversion rate of the polymerization catalyst but also affects the physical properties of the polymer, and may even lead to production shutdowns or stoppages, resulting in decreased plant efficiency and economic benefits. Therefore, trace amounts of oxygen in olefin gases must be efficiently removed.

[0003] In modern industry, deoxygenation and purification have a wide range of applications. With the development of industries such as electronics, semiconductor materials, metallurgy, and petrochemicals, there are diverse and multi-level demands for deoxygenation methods and deoxygenating agents, with different types, application conditions, and effects.

[0004] Currently, there are three main categories of deoxidizers commonly used for removing trace oxygen from olefin gases: The first category consists of physical adsorption deoxidizers, such as activated carbon and molecular sieves, which utilize their large specific surface area and strong adsorption capacity for adsorption and deoxygenation. The second category comprises catalytic reaction deoxidizers, often using noble metals such as Pt, Pd, and Ag as active components, impregnated and loaded onto supports such as alumina, silica, molecular sieves, activated carbon, and titanium dioxide. In the presence of hydrogen, a catalytic reaction occurs between hydrogen and oxygen to produce water, thus removing the oxygen. The third category consists of chemical adsorption reaction deoxidizers, which often use transition metal elements with d5, d7, d8, and d10 structures such as Cu, Mn, Co, Mo, Ni, and Cr as active components, and alumina, silica, and magnesium oxide as supports. Through hydrogen reduction, the reduced active component or its low-valence metal oxide reacts with trace oxygen in the gas to generate high-valence oxides, thereby removing the oxygen.

[0005] Patent CN101745391A discloses a precious metal deoxidizer for removing trace amounts of oxygen from catalytic cracking dry gas. The catalyst uses alumina, activated carbon, silica, or molecular sieves as supports, palladium as the main active component, and one or more of Ag, Au, Co, and Cr as co-catalytic active components. The catalytic active components are distributed in an eggshell-like pattern on the support surface. This catalyst has a high precious metal content, operates at high temperatures, and suffers significant ethylene loss when used for deoxygenating catalytic cracking dry gas.

[0006] Patent CN115025779A discloses a catalyst for removing trace amounts of oxygen from olefins, using alumina as a support, palladium and manganese oxide as the main catalytically active components, and one or more of copper, silver, and gold as co-catalytically active components. This catalyst is granular or strip-shaped and treats gases with low hydrogen content.

[0007] Patent CN103157471A discloses an olefin deoxygenation catalyst that uses a titanium-aluminum composite oxide as a carrier, one or more of palladium, platinum, and silver as active components, and any one of manganese, iron, cobalt, copper, and zinc as an auxiliary agent. This deoxygenator requires a high content of precious metals for low-temperature (≤100℃) deoxygenation.

[0008] Patent CN 100341606A discloses a bifunctional deoxidizer with palladium and manganese as active components and its production method, which is mainly used for the removal of trace oxygen from syngas, hydrogen and nitrogen.

[0009] Patent CN101165030A discloses a deoxidizer with dual Mn-Ag active components and calcium aluminate as a carrier, which can remove trace oxygen from ethylene and propylene to below 0.05 ppm at room temperature. This deoxidizer requires repeated regeneration during use to maintain its deoxidizing activity.

[0010] Deoxygenation processes, whether catalytic or chemisorption, are exothermic. The deoxygenation process involving the catalytic reaction of hydrogen and oxygen to produce water is particularly exothermic; removing even a fraction of oxygen can cause a temperature rise of tens of degrees Celsius in the feed gas. This significantly increases the difficulty of steady-state control and greatly increases the likelihood of side reactions, such as the addition reaction of hydrogen to olefins. Existing deoxygenation catalysts are typically granular or strip-shaped and are usually applied using a stacking reaction method, which does not help dissipate heat or suppress side reactions.

[0011] In industrial processes for removing trace amounts of oxygen from hydrogen-rich olefin feed gas, the hydrogen and oxygen content of the feed gas entering the deoxidation tower is generally limited. That is, hydrogen is removed from the hydrogen-rich olefin feed gas first, and then a small, appropriate amount of hydrogen is added. This is because the heat of reaction in the deoxidation reaction and the potential side reactions such as the addition reaction between hydrogen and olefins could lead to uncontrollable processes and damage to the deoxidation effect and the deoxidizing agent. Summary of the Invention

[0012] Existing processes for removing trace amounts of oxygen from hydrogen-rich olefin feed gas typically require the step of "first removing hydrogen from the hydrogen-rich olefin feed gas, and then adding a small amount and appropriate amount of hydrogen." This invention provides a catalyst for removing trace amounts of oxygen from hydrogen-rich olefin gas, its preparation method, and a catalytic removal method.

[0013] This invention achieves a novel catalyst by employing an integral support, coating the support surface with an alumina layer, and simultaneously adjusting the content of the main active component and the active additives in the catalyst. When using the catalyst of this invention to remove trace amounts of oxygen from hydrogen-rich olefin feed gas, there is no need to remove hydrogen before adding it; the hydrogen-rich olefin feed gas can directly contact the catalyst of this invention. Even with the presence of hydrogen at a molar content as high as 20%, no significant side reactions will occur.

[0014] The catalyst of this invention is used to catalytically remove trace amounts of oxygen from hydrogen-rich olefin gases. The process is simple, requires a low reaction temperature, has a high olefin retention rate, and provides good deoxygenation effect.

[0015] One of the objectives of this invention is to provide a catalyst for removing trace amounts of oxygen from hydrogen-rich olefin gases.

[0016] The catalyst is composed of an integral support, a main active component, and an active auxiliary agent;

[0017] The integral carrier is a honeycomb ceramic coated with an alumina coating;

[0018] The main active component is the noble metal palladium;

[0019] The active additive contains at least one of silver, manganese, cobalt, and copper.

[0020] The main active component has a weight content of 0.01-0.5% relative to the monolithic carrier, preferably 0.01-0.1%, more preferably 0.01-0.05%; for example: 0.01%, 0.02%, 0.035%, 0.04%, 0.05%.

[0021] The active ingredient can be silver and manganese; the mass ratio of silver to manganese can be any ratio, preferably 0.8:10. The active ingredient can be cobalt. The active ingredient can be copper and manganese; the mass ratio of copper to manganese can be any ratio, preferably 3.5:9.

[0022] The active additive has a weight content of 0.1% to 20% relative to the monolithic carrier, preferably 0.1% to 15%, more preferably 10% to 15%; for example: 10.8%, 14%, 12.5%.

[0023] The specific surface area of ​​the integral carrier is greater than 120m². 2 / g, mechanical strength higher than 2.6kN / cm 2 .

[0024] The honeycomb ceramic can be any existing honeycomb ceramic capable of loading the main active component and the active additive; preferably, it is cordierite honeycomb ceramic.

[0025] The catalyst is a monolithic catalyst supported on a honeycomb ceramic carrier. The catalyst has palladium as the main active component and at least one of silver, manganese, cobalt, and copper as an active additive; the main active component and the active additive are uniformly mixed and loaded onto the honeycomb ceramic.

[0026] Compared to existing catalysts, the catalyst provided by this invention has an integral support, which significantly reduces the content of the main active component and significantly increases the content of the active additive; its catalytic effect is not reduced, but rather achieves good catalytic effect at low temperatures.

[0027] The catalyst provided by this invention not only possesses advantages such as low precious metal content and low activation temperature, but also facilitates rapid conduction and dissipation of the heat of hydrogen-oxygen reaction and helps achieve low-temperature operation throughout the reaction process, thereby significantly suppressing or even avoiding side reactions (olefin hydrogenation reactions). This allows for direct trace oxygen removal from hydrogen-rich olefin feedstock gas without the need for prior hydrogen removal and re-addition, simplifying the process. This has application advantages and practical value in the removal of trace oxygen from various olefins, refinery dry gases, and especially high-hydrogen-content olefin gases.

[0028] A second objective of this invention is to provide a method for preparing the catalyst described in one of the objectives of the invention.

[0029] The preparation method includes: preparing honeycomb ceramics into honeycomb ceramics coated with alumina, and then immersing them in an impregnation solution, drying them, and reducing them;

[0030] The impregnation solution contains soluble compounds of the main active component, soluble compounds of the active additives, surfactants, acids, and water.

[0031] The soluble compound of the main active component can be any existing soluble compound of the main active component, and those skilled in the art can choose according to the actual situation. As one option, palladium nitrate is selected as the soluble compound of the main active component.

[0032] The soluble compound of the active agent can be any existing soluble compound selected from at least one of silver, manganese, cobalt, and copper, and those skilled in the art can choose according to the actual situation. As one option, the soluble compound of the active agent is selected from one or more of silver nitrate, manganese nitrate, cobalt nitrate hexahydrate, and copper nitrate trihydrate. For example, silver nitrate and manganese nitrate can be used, or cobalt nitrate hexahydrate can be used, or cobalt nitrate hexahydrate and copper nitrate trihydrate can be used. When two or more of silver nitrate, manganese nitrate, cobalt nitrate hexahydrate, and copper nitrate trihydrate are used, their proportions can be arbitrary.

[0033] The surfactant can be any conventional surfactant in the art, and those skilled in the art can select one according to the actual situation. Specifically, the surfactant can be selected from at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and sec-octyl alcohol polyoxyethylene ether.

[0034] The acid can be any commonly used acid in the art, and those skilled in the art can choose according to the actual situation. Specifically, the acid can be dilute hydrochloric acid or dilute nitric acid.

[0035] In the impregnation solution, the concentrations of soluble compounds of the main active component, soluble compounds of the active additives, surfactants, and acids can be selected within a wide range. Those skilled in the art can determine this based on the specific circumstances. As a preferred embodiment, the concentration of the surfactant in the impregnation solution is 1–5 wt%.

[0036] In the preparation method, impregnation, drying, and reduction can all be performed using conventional operations in the art. To ensure that the main active component and active additive are uniformly mixed together and co-loaded on the honeycomb ceramic, the impregnation is performed in a one-step impregnation method, that is, the integral carrier is impregnated in an impregnation solution containing both the main active component and the active additive.

[0037] The preparation method includes the following steps:

[0038] (1) After activation treatment, the honeycomb ceramic is immersed in aluminum sol, taken out, the residual liquid is blown off, dried and calcined to obtain a honeycomb ceramic with an aluminum oxide coating.

[0039] (2) Impregnation: Immerse the honeycomb ceramic coated with alumina in the impregnation solution and impregnate it thoroughly;

[0040] (3) Drying: Dry the impregnated honeycomb ceramic at 80-150℃ for 0.5-5 hours;

[0041] (4) Repeat steps (2) and (3) in sequence until the content of the main active component and active additive on the honeycomb ceramic meets the standard. Dry at 80-150℃ for 3-12 hours and calcine at 400-600℃ for 1-6 hours to obtain the catalyst precursor.

[0042] (5) Reduction: The catalyst precursor is reduced in the liquid phase with hydrazine hydrate as a reducing agent, or reduced in the gas phase under a hydrogen atmosphere to obtain the catalyst.

[0043] In the preparation method, the monolithic support is activated before impregnation. On the one hand, the activation treatment can open up and enrich the pores of the support, making it easier for the main active component and active additives to enter the support; on the other hand, after the activation treatment, the binding force between the main active component, active additives and the support is improved, and the stability of the catalyst is improved.

[0044] The activation can be performed using conventional methods in the art. Specifically, step (1) activation includes: immersing the honeycomb ceramic in a 3-15 wt% nitric acid solution, allowing it to stand at 100-220°C for 1-5 hours under sealed conditions, rinsing it with deionized water until neutral, drying it at 80-150°C for 3-12 hours, and calcining it at 400-600°C for 1-6 hours. The concentration of the nitric acid solution is preferably 5-10 wt%.

[0045] In step (1), the aluminum sol is prepared by adding boehmite to deionized water, adding concentrated nitric acid dropwise while stirring, slowly heating to 50-90°C, adding until completely dissolved and controlling the pH value to 2-5, aging for 12-48 hours to obtain transparent aluminum sol.

[0046] One specific embodiment of the preparation method includes:

[0047] (1) Take cordierite honeycomb ceramic, immerse it completely in 3-15wt% nitric acid solution, perform closed hydrothermal activation treatment at 100-220℃ for 1-5 hours, then rinse with deionized water until neutral and dry at 80-150℃ for 3-12 hours, and calcine at 400-600℃ for 1-6 hours to obtain surface-activated cordierite honeycomb ceramic;

[0048] (2) Add boehmite to deionized water, add concentrated nitric acid dropwise while stirring, heat slowly to 50-90°C, add dropwise until completely gelled and control the pH value to 2-5, age for 12-48 hours to obtain transparent aluminum sol;

[0049] (3) The surface-activated cordierite honeycomb ceramic is completely immersed in the transparent aluminum sol in step (2) for 5-10 minutes, then removed, the residual liquid in the channel is blown away, and after drying and calcination, the cordierite honeycomb ceramic carrier with aluminum oxide coating is obtained.

[0050] (4) Weigh the soluble compounds of the main active component, the soluble compounds of the active additives, the surfactant and the acid together and dissolve them in water to prepare an acid impregnation solution; the content of palladium in the soluble compounds of the main active component relative to the overall carrier is 0.01 to 0.5%, and the content of the active additives in the soluble compounds of the active additives relative to the overall carrier is 0.1 to 20%.

[0051] (5) The cordierite honeycomb ceramic carrier coated with alumina is completely immersed in an acid-containing impregnation solution. After thorough impregnation, it is taken out and dried at 80-150℃ for 0.5-5 hours. The impregnation and drying are repeated until the acid-containing impregnation solution is completely absorbed by the cordierite honeycomb ceramic. Finally, it is dried at 80-150℃ for 3-12 hours and calcined at 400-600℃ for 1-6 hours to obtain the catalyst precursor.

[0052] (6) The catalyst precursor is reduced in the liquid phase by hydrazine hydrate or in the gas phase under a hydrogen atmosphere to obtain the catalyst.

[0053] The third objective of this invention is to provide a method for the catalytic removal of trace oxygen from hydrogen-rich olefin gases.

[0054] The method includes: directly contacting a hydrogen-rich olefin gas with the catalyst described in one of the invention objectives or the catalyst prepared by the method described in another invention objective. The hydrogen-rich olefin gas does not require prior hydrogen removal and addition; it directly contacts the catalyst.

[0055] Specifically, this includes: in a fixed-bed reactor, hydrogen-rich olefin gas is directly contacted with the catalyst, at a reaction temperature of room temperature to 120°C, a pressure of 0.1 to 2 MPa, and a space velocity of 2000 to 20000 h⁻¹. -1 Under these conditions, the deoxygenation reaction takes place;

[0056] Preferably, the reaction is carried out at a temperature of room temperature to 80°C, a pressure of 0.1 to 1 MPa, and a space velocity of 3000 to 10000 h⁻¹. -1 The deoxygenation reaction takes place under certain conditions.

[0057] At the inlet of the fixed-bed reactor, the oxygen concentration of the hydrogen-rich olefin gas does not exceed 3000 ppm and the hydrogen molar content does not exceed 20%.

[0058] Preferably, at the inlet of the fixed-bed reactor, the oxygen concentration of the hydrogen-rich olefin gas does not exceed 2000 ppm and the hydrogen molar content does not exceed 15%.

[0059] The present invention provides a catalytic removal method for trace oxygen in hydrogen-rich olefin gas. The hydrogen-rich olefin gas directly contacts the catalyst to carry out the deoxygenation reaction, eliminating the need for the cumbersome step of first removing hydrogen from the hydrogen-rich olefin gas and then adding an appropriate amount of hydrogen. The process is simple.

[0060] Although hydrogen-rich olefin gases contain a high amount of hydrogen, the above-mentioned catalytic removal method, by employing the catalyst of the present invention, reduces the occurrence of side reactions between the high hydrogen content and olefins during the catalytic removal of trace amounts of oxygen, resulting in an olefin retention rate of over 99.5%.

[0061] The catalytic removal method for trace oxygen in hydrogen-rich olefin gases provided by this invention does not require high temperature conditions and can be carried out at room temperature.

[0062] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0063] The catalyst provided by this invention is a monolithic catalyst, which is different from granular or strip-shaped catalysts. The monolithic catalyst provided by this invention does not require a stacking reaction method during use, which helps to dissipate heat and suppress side reactions.

[0064] The catalyst provided by this invention uses an integral honeycomb ceramic as a carrier, which makes the catalyst have high overall mechanical strength and stable performance.

[0065] The catalyst provided by this invention has an alumina coating on its support surface. The catalyst has a low noble metal content, highly dispersed main active components, and uniform doping of main active components and active additives. Therefore, its catalytic activity is suitable and selective.

[0066] The catalyst provided by this invention requires a low deoxygenation temperature, reduces catalyst bed pressure, facilitates heat conduction, minimizes temperature differences, and effectively suppresses side reactions. The catalyst is simple to prepare and suitable for industrial production and application.

[0067] The catalytic removal method for trace oxygen in hydrogen-rich olefin gas provided by this invention has simple process steps, does not require high temperature conditions, can be carried out at room temperature, has a high olefin retention rate, and has a good deoxygenation effect. Detailed Implementation

[0068] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0069] All reagents used in the following examples are commercially available products.

[0070] Example 1

[0071] (1) Preparation of a catalyst with a main active component Pd content of 0.03 wt%, an active auxiliary component Ag content of 0.8 wt%, and an active auxiliary component Mn content of 10 wt%:

[0072] A cylindrical cordierite honeycomb ceramic with a diameter of 29.9 mm and a length of 50 mm was completely immersed in a sealed reaction vessel containing a 6 wt% nitric acid solution. It was left to stand at 200°C for 3 hours, then removed, thoroughly washed with deionized water, dried at 120°C for 4 hours, and finally calcined at 450°C for 4 hours to obtain a specific surface area of ​​138 m². 2 / g of activated cordierite honeycomb ceramic carrier;

[0073] Add 150g of boehmite to 50g of deionized water, add concentrated nitric acid dropwise while stirring, and slowly heat to 80℃. Continue adding until completely dissolved and control the pH value at 2-5. Let it age for 24 hours to obtain a transparent aluminum sol.

[0074] After the activated cordierite honeycomb ceramic carrier is completely immersed in aluminum sol for 5 minutes, it is taken out, the residual liquid in the pores of the honeycomb ceramic carrier is blown away, dried at 110℃ for 6 hours, and then calcined at 500℃ for 4 hours to obtain cordierite honeycomb ceramic carrier with aluminum oxide coating.

[0075] Weigh 0.33 g of palladium nitrate and 6.30 g of silver nitrate and dissolve them in 40 g of water. Then add 325.7 g of 50 wt% manganese nitrate solution to the above solution, and then add 10 g of 27.2 wt% dilute nitric acid and 7.8 g of surfactant polyoxyethylene fatty alcohol ether (RO(CH2CH2O)5H, R is C7~C9) to form a uniform impregnation solution.

[0076] 500g of cordierite honeycomb ceramic coated with alumina was completely immersed in the impregnation solution. After thorough impregnation, it was removed and dried at 110℃ for 4h. The impregnation and drying steps were repeated until the impregnation adsorption reached the required loading. Finally, it was dried at 110℃ for 8h and calcined at 450℃ for 4h to obtain a catalyst precursor with a main active component Pd content of 0.03wt%, an active auxiliary agent Ag content of 0.8wt%, and an active auxiliary agent Mn content of 10wt%.

[0077] The catalyst precursor was reduced at 200°C in a hydrogen atmosphere for 6 hours to obtain the catalyst.

[0078] (2) Catalytic removal of trace oxygen from hydrogen-rich olefin gases:

[0079] The catalyst prepared in step (1) was placed in a fixed-bed reactor. Standard hydrogen-rich olefin feed gas was introduced at a space velocity of 5000 h⁻¹. -1 The gas directly enters the fixed-bed reactor and comes into direct contact with the catalyst, reacting at 0.3 MPa and 45°C. The standard hydrogen-rich olefin feed gas at the inlet of the fixed-bed reactor has the following molar percentage composition: hydrogen 15%, oxygen 1000 ppm, ethylene 20%, ethane 15%, with the remainder being nitrogen balance gas. The gas content at the outlet of the fixed-bed reactor was measured; its oxygen content was below 1 ppm, and the ethylene retention rate was above 99.5%.

[0080] Example 2

[0081] (1) Preparation of a catalyst with a main active component Pd content of 0.05wt% and an active auxiliary component Co content of 14wt%:

[0082] A cylindrical cordierite honeycomb ceramic with a diameter of 29.9 mm and a length of 50 mm was completely immersed in a sealed reaction vessel containing a 9 wt% nitric acid solution. It was left to stand at 190°C for 4 hours, then removed, thoroughly washed with deionized water, dried at 120°C for 4 hours, and finally calcined at 450°C for 4 hours to obtain a specific surface area of ​​150 m². 2 / g of activated cordierite honeycomb ceramic carrier;

[0083] Add 150g of boehmite to 50g of deionized water, add concentrated nitric acid dropwise while stirring, and slowly heat to 80℃. Continue adding until completely dissolved and control the pH value at 2-5. Let it age for 24 hours to obtain a transparent aluminum sol.

[0084] After the activated cordierite honeycomb ceramic carrier is completely immersed in aluminum sol for 5 minutes, it is taken out, the residual liquid in the pores of the honeycomb ceramic carrier is blown away, dried at 110℃ for 6 hours, and then calcined at 500℃ for 4 hours to obtain cordierite honeycomb ceramic carrier with aluminum oxide coating.

[0085] Weigh out 0.55 g of palladium nitrate and 19.72 g of cobalt nitrate hexahydrate and dissolve them in 200 g of water. Add 14.9 g of 27.2 wt% dilute nitric acid and 6.0 g of surfactant sec-octanol polyoxyethylene ether (C8H2O). 17 (CH2CH2O)nH, n=1~6), to form a uniform impregnation solution;

[0086] 500g of cordierite honeycomb ceramic carrier coated with alumina was completely immersed in the impregnation solution. After thorough impregnation, it was removed and dried at 110℃ for 4h. The impregnation and drying steps were repeated until the impregnation adsorption reached the required loading. Finally, it was dried at 110℃ for 8h and calcined at 500℃ for 3h to obtain a catalyst precursor with a main active component Pd content of 0.05wt% and an active auxiliary agent Co content of 14wt%.

[0087] The catalyst precursor was reduced at 200°C in a hydrogen atmosphere for 6 hours to obtain the catalyst.

[0088] (2) Catalytic removal of trace oxygen from hydrogen-rich olefin gases:

[0089] The catalyst prepared in step (1) was placed in a fixed-bed reactor. Standard hydrogen-rich olefin feed gas was introduced at a space velocity of 7000 h⁻¹. -1 The gas directly enters the fixed-bed reactor and comes into direct contact with the catalyst, reacting under atmospheric pressure and at 60°C. The standard hydrogen-rich olefin feed gas at the inlet of the fixed-bed reactor has the following molar percentage composition: hydrogen 15%, oxygen 1000 ppm, ethylene 20%, ethane 15%, with the remainder being nitrogen balance gas. The gas content at the outlet of the fixed-bed reactor was measured, and its oxygen content was less than 1 ppm, with an ethylene retention rate of over 99.5%.

[0090] Example 3

[0091] (1) Preparation of a catalyst with a main active component Pd content of 0.04 wt%, an active auxiliary component Cu content of 3.5 wt%, and an active auxiliary component Mn content of 9 wt%:

[0092] A cylindrical cordierite honeycomb ceramic with a diameter of 29.9 mm and a length of 50 mm was completely immersed in a sealed reaction vessel containing a 9 wt% nitric acid solution. It was allowed to stand at 210°C for 2 hours, then removed, thoroughly washed with deionized water, dried at 120°C for 4 hours, and finally calcined at 450°C for 4 hours to obtain a specific surface area of ​​135 m². 2 / g of activated cordierite honeycomb ceramic carrier;

[0093] Add 150g of boehmite to 50g of deionized water, add concentrated nitric acid dropwise while stirring, and slowly heat to 80℃. Continue adding until completely dissolved and control the pH value at 2-5. Let it age for 24 hours to obtain a transparent aluminum sol.

[0094] After the activated cordierite honeycomb ceramic carrier is completely immersed in aluminum sol for 5 minutes, it is taken out, the residual liquid in the pores of the honeycomb ceramic carrier is blown away, dried at 110℃ for 6 hours, and then calcined at 500℃ for 4 hours to obtain cordierite honeycomb ceramic carrier with aluminum oxide coating.

[0095] Weigh 0.44 g of palladium nitrate and 66.53 g of copper nitrate trihydrate and dissolve them in 50 g of water. Then add 293.2 g of 50 wt% manganese nitrate solution to the above solution, followed by 10.3 g of 27.2 wt% dilute nitric acid and 8.4 g of surfactant polyoxyethylene fatty alcohol ether (RO(CH2CH2O)5H, where R is C7-C9) to form a uniform impregnation solution.

[0096] 500 grams of activated cordierite honeycomb ceramic were completely immersed in the impregnation solution. After thorough impregnation, the ceramic was removed and dried at 110°C for 4 hours. The impregnation and drying steps were repeated until the impregnation adsorption reached the required loading. Finally, the ceramic was dried at 110°C for 8 hours and calcined at 450°C for 4 hours to obtain a catalyst precursor with a main active component Pd content of 0.04 wt%, an active auxiliary component Cu content of 3.5 wt%, and an active auxiliary component Mn content of 9 wt%.

[0097] The catalyst precursor was reduced with a 5 wt% hydrazine hydrate aqueous solution for 8 hours, then washed with deionized water until neutral, and dried at 120°C to obtain the catalyst.

[0098] (2) Catalytic removal of trace oxygen from hydrogen-rich olefin gases:

[0099] The catalyst prepared in step (1) was placed in a fixed-bed reactor. Standard hydrogen-rich olefin feed gas was introduced at a space velocity of 4000 h⁻¹. -1The gas directly enters the fixed-bed reactor and comes into direct contact with the catalyst, reacting at 0.5 MPa and 40°C. The standard hydrogen-rich olefin feed gas at the inlet of the fixed-bed reactor has the following molar percentage composition: hydrogen 15%, oxygen 1000 ppm, ethylene 20%, ethane 15%, with the remainder being nitrogen balance gas. The gas content at the outlet of the fixed-bed reactor was measured; its oxygen content was below 1 ppm, and the ethylene retention rate was above 99.5%.

Claims

1. A catalyst for removing trace amounts of oxygen from hydrogen-rich olefin gases, characterized in that, The catalyst is composed of an integral support, a main active component, and an active auxiliary agent; The integral carrier is a honeycomb ceramic coated with an alumina coating; The main active component is the noble metal palladium; The active additive contains at least one of silver, manganese, cobalt, and copper.

2. The catalyst according to claim 1, characterized in that, The main active component has a weight content of 0.01-0.5% relative to the monolithic carrier, preferably 0.01-0.1%; or / and, The active additive has a weight content of 0.1-20% relative to the monolithic carrier, preferably 0.1-15%.

3. The catalyst according to claim 1, characterized in that, The specific surface area of ​​the integral carrier is greater than 120m². 2 / g, mechanical strength higher than 2.6kN / cm 2 .

4. The catalyst according to claim 1, characterized in that, The honeycomb ceramic is cordierite honeycomb ceramic.

5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that, The preparation method includes: preparing honeycomb ceramics into honeycomb ceramics coated with alumina, and then immersing them in an impregnation solution, drying, calcining, and reducing them; The impregnation solution contains soluble compounds of the main active component, soluble compounds of the active additives, surfactants, acids, and water; Preferably, the concentration of the surfactant in the impregnation solution is 1-5 wt%.

6. The preparation method according to claim 5, characterized in that, The soluble compound of the main active component is palladium nitrate; or / and, The soluble compound of the active additive is selected from one or more of silver nitrate, manganese nitrate, cobalt nitrate hexahydrate, and copper nitrate trihydrate; or / and, The surfactant is selected from at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and 2-octyl alcohol polyoxyethylene ether; or / and, The acid is dilute hydrochloric acid or dilute nitric acid.

7. The preparation method according to claim 5, characterized in that, Includes the following steps: (1) After activation treatment, the honeycomb ceramic is immersed in aluminum sol, taken out, the residual liquid is blown off, dried and calcined to obtain honeycomb ceramic with aluminum oxide coating. (2) Impregnation: Immerse the honeycomb ceramic coated with alumina in the impregnation solution and impregnate it thoroughly; (3) Drying: Dry the impregnated honeycomb ceramic at 80-150℃ for 0.5-5 hours, preferably 1-4 hours; (4) Repeat steps (2) and (3) in sequence until the content of the main active component and active additive on the honeycomb ceramic meets the standard. Dry at 80-150℃ for 3-12 hours and calcine at 400-600℃ for 1-6 hours to obtain the catalyst precursor. (5) Reduction: The catalyst precursor is reduced in the liquid phase with hydrazine hydrate as a reducing agent, or reduced in the gas phase under a hydrogen atmosphere to obtain the catalyst.

8. The preparation method according to claim 7, characterized in that, In step (1), the activation treatment includes: immersing the honeycomb ceramic in a 3-15 wt% nitric acid solution, sealing it, and allowing it to stand at 100-220°C for 1-5 hours; rinsing it with deionized water until neutral; drying it at 80-150°C for 3-12 hours; and calcining it at 400-600°C for 1-6 hours to obtain surface-activated honeycomb ceramic; preferably, the concentration of the nitric acid solution is 5-10 wt%; or / and, In step (1), the aluminum sol is prepared by adding boehmite to deionized water, adding concentrated nitric acid dropwise while stirring, slowly heating to 50-90°C, adding until completely dissolved and controlling the pH value to 2-5, aging for 12-48 hours to obtain transparent aluminum sol.

9. A method for the catalytic removal of trace oxygen from hydrogen-rich olefin gas, characterized in that, The hydrogen-rich olefin gas is directly contacted with the catalyst according to any one of claims 1 to 4 or the catalyst prepared by the preparation method according to any one of claims 5 to 8.

10. The catalytic removal method as described in claim 9, characterized in that, The method includes: in a fixed-bed reactor, direct contact between hydrogen-rich olefin gas and the catalyst, at a reaction temperature of room temperature to 120°C, a pressure of 0.1 to 2 MPa, and a space velocity of 2000 to 20000 h⁻¹. -1 Under these conditions, the deoxygenation reaction takes place; Preferably, the reaction is carried out at a temperature of room temperature to 80°C, a pressure of 0.1 to 1 MPa, and a space velocity of 3000 to 10000 h⁻¹. -1 The deoxygenation reaction takes place under certain conditions.

11. The catalytic removal method as described in claim 10, characterized in that, At the inlet of the fixed-bed reactor, the oxygen concentration of the hydrogen-rich olefin gas does not exceed 3000 ppm and the hydrogen molar content does not exceed 20%. Preferably, at the inlet of the fixed-bed reactor, the oxygen concentration of the hydrogen-rich olefin gas does not exceed 2000 ppm and the hydrogen molar content does not exceed 15%.

Citation Information

Patent Citations

  • Double functional deoxidation agent and production process thereof

    CN100341606C

  • Mn-Ag double active components desoxidant, preparation method and application thereof

    CN101165030A

  • Catalyst for removing traces of oxygen in catalytic cracking dry gas

    CN101745391A

  • Deoxidation catalyst for olefin gas, preparation method and application thereof

    CN103157471A